Self-Centering Capacity of a Structural Frame Composed of Steel-Jacketed Concrete Columns and Steel Beams. (June 2018) - Nakahara, Hiroyuki; Yin, Hao
Abstract: A structural frame composed of steel-jacketed concrete columns and steel beams with damage control capacity has been studied for the structural performances through the experiments. Four specimens, which were 1/3 scaling model of cruciform subassemblies, were made and subjected to cyclic force in order to be investigated on its self-centering capacities mainly. The test results showed that this structure remained lower damage after the cyclic loading test than the normal reinforced concrete structure. The load carrying capacities of the specimens were estimated through full plastic moment of the section of the column by taking into consideration of the confining effect of concrete jacketed by steel tube.